Altered eIF6 and Dicer expression is associated with clinicopathological features in ovarian serous carcinoma patients. - Flavin, R; Smyth, P; Finn, S; Laios, A; O'Toole, SA; Barrett, C; Ring, M; Denning, K; Li, J; Aherne, S; Aziz, N; Alhadi, A; et al. (2008)
MicroRNAs are a group of small non-coding RNAs approximately 22 nucleotides in length. Recent work has shown differential expression of mature microRNAs in human cancers. Production and function of microRNAs require coordinated processing by proteins of the microRNA machinery. Dicer and Drosha (RNase III endonucleases) are essential components of the microRNA machinery. Recently, the ribosome anti-association factor eIF6 has also been found to have a role in microRNA-mediated post-transcriptional silencing. We characterized the alterations in the expression of genes encoding proteins of microRNA machinery in ovarian serous carcinoma. Protein expression of eIF6 and Dicer was quantified in a tissue microarray of 66 ovarian serous carcinomas. Dicer, Drosha and eIF6 mRNA expression was analysed using quantitative reverse transcription-PCR on an independent set of 50 formalin-fixed, paraffin-embedded ovarian serous carcinoma samples. Expression profiles of eIF6 and Dicer were correlated with clinicopathological and patient survival data. We provide definitive evidence that eIF6 and Dicer are both upregulated in a significant proportion of ovarian serous carcinomas and are associated with specific clinicopathological features, most notably low eIF6 expression being associated with reduced disease-free survival. The status of eIF6 and proteins of the microRNA machinery may help predict toxicity and susceptibility to future interfering RNA-based therapy.